Belajar Dari Pengalaman : Strategi Adaptasi Tiga Penyandang Disabilitas di Tempat Kerja Informal Meulaboh - Misya Azzahra (Indo Publishing, 2025)
This qualitative research is an exploratory preliminary study aimed at understanding adaptation strategies and social support acceptance among three women with disabilities who actively work in the informal sector in Meulaboh. The geographical conditions of Meulaboh as a coastal region of Aceh present unique challenges in implementing inclusive employment rights guaranteed by the 1945 Constitution and Law No. 8 of 2016. The study employed in-depth interviews and simple observation with three participants who have diverse physical disabilities and work in the informal sector, including sabiki bait tie manufacturing, tailoring, and cake/salted snack production. Thematic analysis identified five interrelated multidimensional adaptation strategies: (1) Work Process Adaptation (tool modification, task division, work method adjustment); (2) Utilization of Social Networks (family, community, customers) as economic infrastructure and emotional support; (3) Building Independence as rejection of charity object status; (4) Resistance Against Stigma through demonstration of work ability, vocal advocacy, and confrontation of systemic discrimination; and (5) Advocating for Equal Opportunity Rights by voicing criticism against discriminatory policies and practices. Participants demonstrated high agency by actively creating inclusive workspaces for themselves, proving that physical limitations do not hinder work productivity. These findings affirm the relevance of the social model of disability, in which the primary barriers stem from inaccessible and non-inclusive environments and systems. Practical implications of the research include the need for more accessible training programs (including transportation provision), support focused on skill development and raw material subsidies for sustained independence, increased transparency in social assistance distribution, and strict enforcement of laws against employment discrimination.